Aportes actuales de la antropología dental a la comprensión del género Homo - Bollini, Gabriel A. (2016)
Human evolutionary studies have received substantial contributions from dental anthropology throughout their history. Dental anthropology has established taxonomic criteria, deduced phylogenetic relationships, deter-mined paleo-dietary implications, studied food processing technologies, and helped to elucidate human behavioral patterns. Various dental analysis approaches, currently used for addressing different issues related to genus Homo, are discussed in this paper. The analysis on the remains recovered from the sites of Dmanisi (Georgia), Sima del Elefante (Spain) and Yiyuan (China) are used as an example. These approaches show that, far from representing just a descriptive perspective, dental analysis provides a bio-cultural approach for the understanding of the genus Homo.